Investigation on bi-layer coating with La2(Ti0.2Zr0.2Sn0.2Ce0.2Hf0.2)2O7/YSZ prepared by laser cladding. Issue 7 (1st April 2023) - Zhang, Dongbo; Feng, Xiaolong; Song, Ruiqing; Wang, Ning; Zhang, Yongsheng
Abstract: Thermal barrier coatings are an effective technology for improving the high-temperature performance of hot section components in gas turbine engine. Due to their excellent properties, high-entropy oxides are considered to be promising materials for thermal barrier coatings. Laser cladding is a coating preparation technology and the top coat prepared by laser cladding technology has an important application value for thermal barrier coatings. In this work, to improve the thermal cycling behavior of the La2 (Ti0.2 Zr0.2 Sn0.2 Ce0.2 Hf0.2 )2 O7 high-entropy oxide coating, a bi-layer coating with the La2 (Ti0.2 Zr0.2 Sn0.2 Ce0.2 Hf0.2 )2 O7 high-entropy oxide layer and the YSZ layer was designed and fabricated by laser cladding on the NiCoCrAlY alloy surface. The microstructure, phase and mechanical properties of the coating were analyzed by X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, and micro-hardness and nanoindentation tests, respectively. The results show that a bi-layer La2 (Ti0.2 Zr0.2 Sn0.2 Ce0.2 Hf0.2 )2 O7 /YSZ coating was successfully prepared by the laser cladding method, and shows good bonding at the interface between the layers. The high-entropy oxide layer maintains a relatively stable defective fluorite structure and its microstructure exists in the stable cellular and dendrite crystalline state after laser cladding. The high-entropy oxide layer prepared by laser cladding showed an average elastic modulus of 167 GPa and an average hardness of 1022.8HV in nanoindentation tests. Thermal cycling of the coating was carried out at 1050 °C. Failure of the bi-layer coating occurred after 60 thermal cycles at 1050 °C. Thermal stresses between different layers are calculated during thermal cycling. Due to its excellent mechanical properties, the bi-layer coating with the La2 (Ti0.2 Zr0.2 Sn0.2 Ce0.2 Hf0.2 )2 O7 high-entropy oxide and YSZ layers is expected to become an effective high-entropy oxide thermal barrier coating.